Examination of Pre-Service Physical Education Teachers' Beliefs on Physical Education Profession - Fatma İlker Kerkez; Derya Sakallı (Selcuk University, 2023)
This research examines pre-service physical education teachers' (PPETs') beliefs on the physical education profession (BPEP). A convergent mixed-method research design was administered. The descriptive information form, PPET-BPEP, and open-ended questions were used to collect the data. 218 PPETs' studying in PETE program and pedagogical formation certificate program participated in this research. Non-parametric tests were used for quantitative data, and content analysis was used for qualitative data. While gender did not differ significantly between the programs, there was a significant difference in the "value of PE profession" sub-domain. There is a substantial difference between those whose first career choice is PE teacher and those who don't, and those who want to become a PE teacher after graduation and those who don't. Those whose first career choice is PE teaching tend to this profession for reasons such as having an athlete identity, dream job, role model effect, and a desire to make children love and teach sports. Those who want to be a PE teacher after graduation stated the following reasons for their preference: want to endear sports to children, love and want to take care of children, dream job, want to explain the importance of the profession, want to be involved in sports and some features of the work. In conclusion, it is recommended that more research should be done on PPETs' beliefs on the PE profession.